Penerapan Metode Inkuiri Untuk Meningkatkan Minat Belajar Peserta Didik Kelas XI MAS Al-Ikhwan Gotowasi Pada Konsep Usaha - Haryati Mahyudin; Ernawati Muhtar (Peneliti.net, 2022)
The variables in this study are; (1). The application of the inquiry method, (2) increase students' interest in learning. This research includes classroom action research (CAR). The aims of this study are: to determine the increase in learning interest of students in class XI MAS Gotowasi. The instruments used in this research are observation and questionnaire sheets. The results in this study using the application of the inquiry method to increase student interest in learning in XIMASal-Ikhwan Gotowasi class can increase interest in learning physics. This is indicated by the increasing interest in learning of students in the high category, namely in the first cycle 28.57% and the second cycle 76.19%.